2023
DOI: 10.1094/phyto-08-22-0313-r
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Melting-Based Marker Development for Wheat Leaf Rust Resistance Gene Lr34

Abstract: Deploying adult plant resistance (APR) against rust diseases is an important breeding objective of most wheat breeding programs. The gene Lr34 is an effective and widely deployed broad spectrum APR gene in wheat against leaf rust fungus Puccinia triticina. Various molecular markers have been developed for Lr34 but, either they require post-PCR handling processes or are not economical. Herein, we developed a high resolution melting (HRM) based diagnostic assay for Lr34 based on a three bp ‘TTC’ deletion in exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The fifth significant SNP (29294) was located on chromosome 5 within the hydroxyproline o-galactosyltransferase galt6 gene. According to our analyses and data in the literature, this gene may be related to the yield of maize because, according to Kaur et al (2023), hydroxyproline o-galactosyltransferase galt6 plays an important role in various stages of plant growth and development [73]. Moreira et al (2023) have reported that arabinogalactan proteins (AGPs) are hydroxyproline-rich, sugar-rich glycoproteins widely distributed in the plant kingdom [74].…”
Section: Discussionmentioning
confidence: 90%
“…The fifth significant SNP (29294) was located on chromosome 5 within the hydroxyproline o-galactosyltransferase galt6 gene. According to our analyses and data in the literature, this gene may be related to the yield of maize because, according to Kaur et al (2023), hydroxyproline o-galactosyltransferase galt6 plays an important role in various stages of plant growth and development [73]. Moreira et al (2023) have reported that arabinogalactan proteins (AGPs) are hydroxyproline-rich, sugar-rich glycoproteins widely distributed in the plant kingdom [74].…”
Section: Discussionmentioning
confidence: 90%
“…Because of frequent changes in pathogen populations, cultivars conferring all-stage resistance genes lose stripe-rust resistance within a short period of time [13]. As a consequence, APR with apparent durability is increasingly being deployed in wheat-breeding and production programs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The gene has been cloned and two allelic variants have been distinguished in it: susceptible (Lr34sus) and resistant (Lr34res) [18,19]. These alleles differ in by 3-nucleotide indel resulting in a deletion of phenylalanine (Phe) at position 546 (exon 11) and a single nucleotide polymorphism (SNP) resulting in a tyrosine (Tyr) to histidine (His) substitution at position 634 (exon 12) in the Lr34Res protein [20,21]. Moreover, additional A/T SNP polymorphisms were discovered in intron 4 and a 1-nucleotide indel in exon 10 that causes a frameshift [18].…”
Section: Introductionmentioning
confidence: 99%